Reliability of finger strength assessment methods in climbing: a systematic review - Pérez-Cordero, J.; Jerez-Mayorga, D.; Rodríguez-Perea, Á.; Soto García, D. (Frontiers in Sports and Active Living, 2025)
Background: This systematic review examined the reliability of finger flexor strength assessments in climbers, addressing the absence of a prior synthesis on this topic. The work is timely given sport climbing's inclusion in the Olympic Games and the growing focus on sport-specific performance diagnostics. Fifteen studies, comprising 747 participants (sample sizes 13-244) with varying skill levels, were included.